Pengaruh Brand Image dan Brand Experience Terhadap Customer Satisfaction dan Brand Loyalty - Triaji, Yudha; Wijayanto, Gatot; Wasnury, Rendra (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2023)
This study aims to analyze the effect of Brand Image and Brand Experience on Customer Satisfaction and Brand Loyalty on Ultra Milk UHT milk customers in Pekanbaru City. This research was conducted on all Ultra Milk uht milk customers who live in Pekanbaru City who have purchased Ultra Milk products. This research consists of four variables, namely one determinant variable, one intervention variable, and two independent variables. These variables are Brand Loyalty (Y2), Customer Satisfaction (Y1), Brand Experience (X2), Brand Image (X1). This research was conducted using a sample of 400 people by distributing questionnaires. The data analysis tool used for hypothesis testing is path analysis with the Partial Least Square (PLS) approach using the SmartPLS ver 3.0 software application. The results of this study state that: 1) brand image has a positive and significant effect on customer satisfaction; 2) brand experience has a positive and significant effect on customer satisfaction; 3) customer satisfaction has a positive and significant effect on brand loyalty; 4) brand image has a positive and significant effect on brand loyalty; 5) brand experience has a positive and significant effect on brand loyalty; 6) brand image has a positive and significant effect on brand loyalty which is intervened by customer satisfaction; 7) brand experience has a positive and significant effect on brand loyalty which is intervened by customer satisfaction.   Abstrak Penelitian ini bertujuan menganalisis pengaruh Brand Image dan Brand Experience terhadap Customer Satisfaction dan Brand Loyalty pada pelanggan susu uht Ultra Milk di Kota Pekanbaru. Penelitian ini dilakukan kepada seluruh pelanggan susu uht Ultra Milk yang berdomisili di Kota Pekanbaru yang pernah melakukan pembelian produk Ultra Milk. Di dalam penelitian ini terdiri dari empat variabel yaitu satu variabel terikat, satu variabel intervening dan dua variabel bebas. Penelitian ini dilakukan dengan menggunakan sampel sebanyak 400 orang dengan penyeberan kuesioner. Alat analisis data yang digunakan untuk pengujian hipotesis adalah analisis jalur dengan pendekatan Partial Least Square (PLS) menggunakan aplikasi perangkat lunak SmartPLS ver 3.0. Hasil penelitian ini menyatakan bahwa: 1) Brand Image berpengaruh positif dan signifikan terhadap customer satisfaction; 2) Brand Experience berpengaruh positif dan signifikan terhadap customer satisfaction; 3) Customer Satisfaction berpengaruh positif dan signifikan terhadap brand loyalty; 4) Brand Image berpengaruh positif dan signifikan terhadap brand loyalty; 5) Brand Experience berpengaruh positif dan signifikan terhadap brand loyalty; 6) Brand Image berpengaruh positif dan signifikan terhadap Brand Loyalty yang diintervening oleh customer satisfaction; 7) Brand Experience  berpengaruh  positif dan signifikan terhadap  Brand Loyalty yang diintervening oleh customer satisfaction.